An Improved Approach of Classical Upper Bound Theory for Stability Analysis of Layered Slopes - ZeRun Tian; YanHong Zhang; XiTong Wei; Fei Li; YaFeng Guo (Advances in Civil Engineering)
The equations for the critical height of layered slope were derived by a related researcher, but they lack details and do not agree with the method of limit equilibrium. So this topic was reinvestigated. Considering the possible global or local failure modes of the layered slope, the equations for the critical height of the above modes are derived based on the upper limit theorem by using rotational failure mechanisms or rotational and translational failure mechanisms. Based on the above theory, the stability coefficients of layered slope are investigated. The results show that the presented upper bound approach has better performance than other methods mentioned in the literature and is consistent with the limit equilibrium method. In combination with the strength reduction method, the global and local stability of the layered slope are analyzed using the several examples. The high-calculation accuracy of presented method and the specific measures to improve the smoothness of the sliding surface are reviewed. From the perspective of the combination of sliding surfaces, the dimensionless parameter vector of the layered slope is introduced. The possible limitations of the upper bound limit approach with log spirals are pointed out and the conditions which must be fulfilled in order to achieve a higher computational accuracy are mentioned.